1982
DOI: 10.1159/000123397
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Osmoregulation in Vertebrates

Abstract: Studies on the roles of prolactin in vertebrate osmoregulation have expanded in recent years to include examination of ionic and osmotic factors contributing to the regulation of secretion by paraneuronal prolactin-secreting cells and the effects of prolactin on a number of ion- and water-transporting epithelial tissues. Coupled with information on whole-animal homeostatic effects, the application of surgical, tissue-culture, biophysical and biochemical techniques to individual components will facilitate broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(48 citation statements)
references
References 70 publications
2
45
0
1
Order By: Relevance
“…3C) and hydromineral disturbance reported by others (Lahlou and Giordan, 1970;Pit et al, 1974;Mazeaud et al, 1977;Pit, 1978;Eddy and Bath, 1979;Eddy, i981). Prolactin is known to help fish maintain homeostasis in FW (Hirano and Mayer-Gostan, 1978;Loretz and Bern, 1982;Hirano, 1986), and lowered plasma osmotic pressure has often been related to increased plasma prolactin level (Prunet et al, 1985;Avella et al, 1990). The potential involvement of prolactin in response to stress in SW is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3C) and hydromineral disturbance reported by others (Lahlou and Giordan, 1970;Pit et al, 1974;Mazeaud et al, 1977;Pit, 1978;Eddy and Bath, 1979;Eddy, i981). Prolactin is known to help fish maintain homeostasis in FW (Hirano and Mayer-Gostan, 1978;Loretz and Bern, 1982;Hirano, 1986), and lowered plasma osmotic pressure has often been related to increased plasma prolactin level (Prunet et al, 1985;Avella et al, 1990). The potential involvement of prolactin in response to stress in SW is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin is believed to act as an osmoregulatory hormone in teleosts and is considered to be of more importance in fresh water (FW) than in seawater (SW) (Hirano and Mayer-Gostan, 1978;Loretz and Bern, 1982;Prunet et al, 1985;Hirano, 1986). Stress is known to cause hydromineral imbalance (Mazeaud et al, 1977;Eddy, 1981) and concomitant elevation in the concentration of the stress hormone cortisol (Mazeaud et al, 1977;Donaldson, 1981;Schreck, 1981).…”
mentioning
confidence: 99%
“…In this regard, PRLs were found to be released from neurohypophyseal endings in response to high potassium and the 14 kDa variant was found in the circulation (Torner et al 1995). Moreover the kidney is a well-known target of neurohypophyseal hormones and of PRL (Hebert et al 1981, Loretz & Bern 1982 and PRL fragments have been shown to bind to renal PRL receptors with higher affinity than PRL itself (Clapp et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Le « cabrit créole » des Antilles Françaises (Chemineau et a/., 1983) a été utilisé dans cette étude pour préciser si cet animal est sensible à son environnement thermique alors qu'il est maintenu à l'extérieur toute la journée « au piquet », mode d'élevage traditionnel dans l'Arc Antillais (Devendra, 1971). En (Loretz et Bern, 1982 . Les Sadhu, 1961 ;Yousef, Kibler et Johnson, 1967).…”
unclassified